Investigation of the Therapeutic Potential of a Synergistic Delivery System through Dual Controlled Release of Camptothecin–Doxorubicin. Issue 6 (21st February 2020) - Zhao, Yongmei; Fletcher, Nicholas L.; Gemmell, Anna; Houston, Zachary H.; Howard, Christopher B.; Blakey, Idriss; Liu, Tianqing; Thurecht, Kristofer J.
Abstract: An ideal nanotherapeutic should enhance therapeutic efficacy of the drug while reducing side effects. This work reports development of a nanotherapeutic utilizing hyperbranched polymers as a platform for conjugating doxorubicin (DOX) and camptothecin (CPT) as potential synergistic therapies. The carrier also includes cyanine‐5 (Cy5) as an imaging tracer to monitor distribution and efficacy of the therapeutic, and a bispecific antibody (BsAb) as a cell targeting agent to increase accumulation and specificity for tumor tissue. The synergism of this drug combination is investigated by utilizing both redox‐ and hydrolytic release mechanisms of CPT and DOX, respectively. Drug release and cellular uptake studies confirm the proposed delivery mechanisms and subsequent intracellular trafficking of the drugs. In this particular case, a superadditive effect is observed in vitro for the two drugs when delivered by nanocarrier. This is enhanced when the carrier is targeted to epidermal growth factor receptor (EGFR) that is upregulated in the tumors. Moreover, tumor regression studies show that the synergistic therapeutic effect of combination nanocarriers has greater inhibition of xenograft tumor growth compared to treatments that deliver DOX or CPT alone, suggesting that codelivery of dual therapeutics using modular hyperbranched polymer carriers offers unique potential to regulate tumor growth. Abstract : Controlled delivery of the drug pair camptothecin and doxorubicin from a targeted nanocarrier leads to enhanced therapeutic response in breast cancer xenografts in mice. Dual‐drug‐loaded hyperbranched polymers targeted to epidermal growth factor receptor using a bispecific antibody shows a synergistic therapeutic effect compared to the drug alone.